Comparison of cytocentrifugation supernatant fluid and formalin‐fixed paraffin‐embedded tissue for targeted next‐generation sequencing. Issue 5 (1st April 2019) - Janaki, Nafiseh; Harbhajanka, Aparna; Michael, Claire W.; Bomeisl, Phillip; Wasman, Jay; Atchley, Maureen; Miskiewicz, Kristina; Alouani, David; Sadri, Navid
Abstract : Background: The emergence of less invasive procedures coupled with the growth of molecular testing have created a need for clinical laboratories to optimize workflows to enable tissue preservation and ancillary testing. In the preparation of formalin‐fixed paraffin‐embedded cell blocks (FFPE CBs), there is a cytocentrifugation step for cell pellet extraction that results in postcentrifugation supernatant fluid (SN). This SN, which in most routine workflows is discarded, has been suggested to contain adequate cellular material for molecular testing. In the current study, the authors describe the use of DNA and RNA extracted from SN for the detection of clinically relevant biomarkers by next‐generation sequencing (NGS). Methods: After cell pellet removal, cytocentrifugation SN from 30 endobronchial fine‐needle aspiration rinses that were positive for malignancy on FFPE CB were collected. DNA and RNA were extracted from the SN and tested using an in‐house NGS Solid Tumor Focus Assay. The NGS results were compared with findings from corresponding FFPE samples. Results: Testing was successful in all 30 samples. There was 100% concordance between variants observed in the SN and corresponding FFPE specimens, which included 50 single‐nucleotide variants, 9 copy number amplifications, 3 structural variants, and 2 indels. Furthermore, there was excellent correlation (correlation coefficient, 0.93) between the variant allele frequency of mutations observed in SN compared with that noted in corresponding FFPE CBs. Conclusions: Cytocentrifugation SN is a valuable source for NGS, is comparable to FFPE that preserves tissue for other ancillary testing, and can reduce the failure rate of testing that may result from insufficient material being available in the CB. Abstract : Cytology supernatant fluid is a robust sample for DNA‐based and RNA‐based next‐generation sequencing. Supernatant fluid can reliably replace formalin‐fixed paraffin‐embedded cell blocks for molecular testing.